Determination of Technological Parameters for Heat Setting of Nylon-Spandex Compression Socks - Ta, Vu Luc; Vu, Thi Hong Khanh (Old Journal, 2019)
The knitted fabric samples are knitted into tubes with polyamide yarns (70D/48F), polyamide covered yarns with spandex core (50D/40D) and bare elastane yarns (420D). The knitted tubes were heat treated to study the simultaneous effects of temperature and heating time on pressure of knitted tube on the body and on the fabric elasticity. The pressure of the samples on the body was determined according to Laplace’s law, the elasticity of the samples was determined according to standard NF-G07-196. The results showed that the pressure of the tube on the body affected by the temperature and the heating time. Elasticity of polyamide–spandex knitted tube has changed little after heat treatment. The highest pressure and high elasticity achieved at 145ºC for 5 minutes.